Exploring the Correlation between Trabecular Meshwork Stripping and IOP Reduction in ab Interno Goniectomy - Sahebaan Sethi (TNOA Journal of Ophthalmic Science and Research)
Minimally invasive glaucoma surgeries (MIGS) offer promising intraocular pressure (IOP) reduction with favorable safety profiles. This article explores whether increasing the extent of trabecular meshwork (TM) excision proportionally enhances IOP lowering outcomes. By critically analyzing recent studies involving varied TM excision angles—from 30° to 360°—we highlight that although wider excisions may yield greater IOP reductions, the benefits tend to plateau beyond 90°, with 360° excision associated with higher complication rates such as hyphema. Evidence suggests that individualized treatment plans based on disease severity and anatomical variability are essential. Further prospective studies are warranted to establish optimal TM excision extents for maximal efficacy and safety in glaucoma management.